KEMAMPUAN SISWA DALAM PROSES PEMECAHAN MASALAH BANGUN DATAR SEGI EMPAT BERDASARKAN TAHAPAN VAN HIELE - Ferry Gunawan; Agung Hartoyo; Rustam Rustam (Jurnal AlphaEuclidEdu, 2022)
This study aims to determine and describe problem solving abilities based on the stages of thinking about rectangular flat shapes. The technique utilized is expressive subjective. The subjects in this study were seventeen students selected at random with the highest scores being selected by three grade VII understudies of SMP Negeri 2 Pemangkat. The data collection technique used is a test that will be given to the selected subject based on problem solving based on Van Hiele's thinking. The results of describing the data show that there are three subjects who are in the Visualization stage, they know the name of the rectangular shape from the visual form without knowing the nature and conditions of the shape, for the analysis stage the three subjects have not reached, students cannot explain and determine the nature of the requested shape and for the stage of abstraction there are no students who reach this stage, judging by the results of their answers that students have not been able to define a rectangular shape in indonesian itself and have not been ready to decide similar properties between one shape and another.